Using Different Methods baseflow Separation of Karst Springs Based on Isotope Content (Case study: Kahman Karst Spring) - Abazar Solgi; Heidar Zarei; Safar Marofi (تحقیقات کاربردی علوم جغرافیایی)
Different methods are used for baseflow separation, filtering method one of these methods. In this study, the filtering methods with different algorithms, inclusive One-Parameter, Two-Parameter, Three-Parameter, Lyne & Hollick, Chapman, Furey & Gupta, Eckhardt and Ewma used for daily baseflow separation of Kahman karst spring in Aleshter county. The statistical period used in this study was a period of 27 years. The Isotope content method used as the main method for baseflow separation. Samples analyzed at the Mesbah Energy Company laboratory. Each algorithm has different parameters. First the parameters of each algorithm optimized based on the isotopic content method in the water year of 2017-2018. Then the optimized parameters used for the period 27 years.  At the end, using the evaluation of different critical compared to the different algorithms. The results showed that the Eckhart algorithm performs better than other algorithms. This algorithm estimated baseflow and surface water indexes, respectively 81 and 19 percent.